Improvement of Salt Tolerance in Durum Wheat (Triticum Durum Desf.) by Auxin and Kenitin Application - Zoubida, Benmakhlouf; Gherroucha, Hocine (European Scientific Journal, ESJ, 2017)
The aim of this work is to study the effect of soil salinity using different levels of NaCl (0, 10, 15 g/ NaCl) on some morphological and physiological properties of durum wheat (Triticum durum Desf.) var KEBIR in the vegetative stage. The results obtained allowed us to observe the negative impact of saline stress on the leaf area, Chlorophyll b, and carotenoids at moderate and higher salinity levels. The effect of salt on chlorophyll a content remains insignificant. On the other hand, proline content was highly affected by salt stress. It was excessively increased with the rise of osmotic stress levels, especially at higher salinity levels (15g/l NaCl). Phytohormones, such as auxin and cytokinin, are known to be involved in the regulation of plant responses to salinity stress. Also, it counteracts the adverse effect of stress conditions. Exogenous spraying of indole-3-acetic acid (IAA) and kinetin (K) with three various levels (10, 20, 30 p.p.m.), during the vegetative phase, indicated that an increase in the leaf area and pigments content are associated with a decrease in the proline content.